Development and validation of sunlight exposure measurement questionnaire (SEM-Q) for use in adult population residing in Pakistan - Humayun Quratulain; Iqbal Romaina; Azam Iqbal; Khan Aysha; Siddiqui Amna; Baig-Ansari Naila (BMC, 2012)
Abstract Background Vitamin D deficiency has been identified as a major public health problem worldwide. Sunlight is the main source of vitamin D and its measurement using dosimeters is expensive and difficult for use in population-based studies. Hence, the aim of this study was to develop and validate questionnaires to assess sunlight exposure in healthy individuals residing in Karachi, Pakistan. Methods Two questionnaires with seven important items for sunlight exposure assessment were developed. Fifty four healthy adults were enrolled based on their reported sunlight exposure (high = 17, moderate = 18, low = 19) from Aga Khan University, Karachi. Over four days, study participants were asked to wear a dosimeter between sunrise and sunset and report time spent and activities undertaken in the sun for questionnaire validation. Algorithm for item weightage was created as an average score based on ultraviolet B percentage received. Blood samples were obtained for serum vitamin D. Results The mean time (minutes) spent in sun over 4 days (±SD) was 69.5 (±32) for low, 83.5 (±29.7) for moderate and 329 (±115) for high exposure group. The correlation between average time (minutes) spent in sun over 4 days and mean change in absorbance of UV dosimeters for 4 days was 0.60 (p < 0.01). Correlation between average score and vitamin D levels was found to be 0.36 (p = 0.01) for short term questionnaire score, 0.43 (p = 0.01) for long term questionnaire score in summers and 0.48 (p = 0.01) in winters. Conclusions The sunlight exposure measurement questionnaires were valid tools for use in large epidemiological studies to quantify sunlight exposure.